Cholangiocarcinoma, sequential chemotherapy, and prognostic tests - Bruckner, Howard W.; De Jager, Robert; Knopf, Elisheva; Bassali, Fred; Book, Abe; Gurell, Daniel; Nghiem, Van; Schwartz, Myron; Hirschfeld, Azriel (Frontiers in Oncology, 2024)
Routine blood tests are prognostic tests for patients with cholangiocarcinoma. New drug regimens may produce a median overall survival of 2 years or more. This single practice, IRB-approved, phase II trial examines prognostic tests, Kaplan-Meier survival, and univariate Cox regression analyses. Eligibility requires: intent-to-treat; signed consent; advanced measurable intrahepatic cholangiocarcinoma, with or without resistance to the test drugs; any adult age; performance status 0–2; and expected survival of ≥ 6 weeks. Biweekly treatment, with 1/3 of standard dosages in mg/M2, includes: Gemcitabine 500; 5-Fluorouracil 1200 over 24 hours; Leucovorin 180; Irinotecan 80; and on day 2, Oxaliplatin 40. On progression, drugs are added on day 2: Docetaxel 25 precedes oxaliplatin with or without Mitomycin C 6 after oxaliplatin. The next sequential additions are day 1, Cetuximab 400 total mg, then 200 mg weekly, and then Bevacizumab 10 mg/kg is substituted for Cetuximab (FDA IND# 119005). For 35 patients, 19 with 1-2 lines of prior therapy, resistant tumors, and 16 with no prior therapy, survival at 24 months is ≥ 72 and ≥ 58%, respectively (P = 0.97). For 14 patients aged ≥ 70 years, ≥ 63% survive 24 months, P = 0.28. Validated tests that predict ≤ 6-month survivals find median survival times of 17-months through > 2-years. When compared to patients with favorable tests: Neutrophil lymphocyte ratio > 3.0, HR = 6.54, P < 6.4x10-3; absolute neutrophil count > 8000/μl, HR = 4.95, P < 6.5x10-3; serum albumin < 3.5 g/dl, HR = 4.10, P < 0.03; and lymphocyte monocyte ratio < 2.1, HR = 1.6, P = 0.50. Overall, the 76 (60–90)% of patients with 0-2 out of 4 high risk tests survive ≥ 24 months (P = 7.1x10-3) when compared to patients with 3–4 out of 4 high risk tests. Treatments produce neither hospitalization, neutropenic fever, severe enteritis, nor severe neuropathies. Two-year survival is replicable and predictable. Findings warrant phase III validation tests of sequential regimens, re-challenge with recombination, low dosages, and of blood tests that are associated with lethal mechanisms that impair response and survival.